Smilax china L. polyphenols alleviates obesity and inflammation by modulating gut microbiota in high fat/high sucrose diet-fed C57BL/6J mice. (February 2021) - Li, Xin; Yang, Licong; Xu, Meng; Qiao, Gaoxiang; Li, ChangJiang; Lin, Lezhen; Zheng, Guodong
Graphical abstract: Highlights: Smilax china L. polyphenols prevents high fat/high sucrose (HFHS)-induced obesity in C57BL/6J mice. Smilax china L. polyphenols reduces pro-inflammatory cytokines and LPS level in obese mice. Smilax china L. polyphenols supplement improved glucose intolerance. Smilax china L. polyphenols alters the composition of the gut microbiota in obese mice. Abstract: This study was to investigate whether Smilax china L. polyphenols (SCLP) could ameliorates high fat/high sucrose (HFHS)-induced obesity and inflammation in mice by modulation of gut microbiota. SCLP was extracted from Smilax china L. rhizome and identified by liquid chromatography tandem mass spectrometry (LC–MS/MS). Then, C57BL/6J mice were fed with Chow diet, HFHS and HFHS supplement with SCLP or Orlistat for 12 weeks. In general, three phenolic acids and three flavonoids were identified from SCLP. The treatment of SCLP efficiently improved glucose tolerance and reduced body weight, fat accumulation, inflammation, and lipid concentrations of serum and liver. Furthermore, SCLP significantly decreased ratios of Firmicutes to Bacteroidetes, relative abundance of Desulfovibrionaceae, Lachnospiraceae, Streptococcaceae, and remarkably increased relative abundance of Akkermansiaceae in the gut. These results suggested that SCLP may be used as potential agents to prevent obesity and related metabolic diseases in HFHS-fed mice.